Kompetensi Guru dalam Pembelajaran di Era Digital - Agung Maulana; Desty Endrawati Subroto; Akifah Putri Asriyani; Rismayanti Rismayanti; Siti Hamdah (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The digital era of the 21st century has introduced transformative changes across various fields, including education. The deployment of digital resources and online services devices has facilitated learning that is more flexible, interactive, and accessible. However, effectively integrating technology into education demands a comprehensive understanding, particularly from educators. This study examines the Problems and Prospects associated with adopting technology in education, with a focus on the Indonesian context. Teachers in the digital age face substantial demands to innovate, develop digital skills, and align teaching methods with the needs of Generation Z, who have grown up surrounded by technology. Teachers who are professional, adaptable, and technologically skilled play a crucial role in driving educational innovation, improving teaching quality, and preparing students to meet the expectations the Fourth Industrial Revolution. This research aims to investigate the potential of technology to enhance educational access, develop innovative teaching approaches, and promote the success of technology-driven learning in Indonesia. The results are expected to offer strategic insights for building an efficient education system tailored to the digital era.